2019
DOI: 10.1177/2158244019853903
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Causal Relationship Between Economic Policy Uncertainty and Exchange Market Pressure in BRIC Countries: Evidence From Bootstrap Panel Granger Causality

Abstract: This study examines the causal relationships between exchange market pressure and both global and domestic economic policy uncertainty among the Brazil, Russia, India, and China economies. We employed the bootstrap panel Granger causality approach, having found cross-sectional dependency among the countries as an indicator of their mutual developmental characteristics. The individual country analysis shows that, between exchange market pressure and global economic policy uncertainty, only China has bidirection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…e possible regional integration of the Asian economy and its contagion effects prevailed during the 1997/98 Asian financial crisis that started in ailand and spread across the subregion. erefore, examining the comovement of EPU among the Asian countries is of great importance because of its impact on array of economic activities such as stock markets, housing price, commodity prices, and many more [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…e possible regional integration of the Asian economy and its contagion effects prevailed during the 1997/98 Asian financial crisis that started in ailand and spread across the subregion. erefore, examining the comovement of EPU among the Asian countries is of great importance because of its impact on array of economic activities such as stock markets, housing price, commodity prices, and many more [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the foreign exchange market is put under immense pressure during periods of high uncertainty and remains relatively calm when uncertainty is low. Olanipekun et al (2019) also established that both domestic and global EPU can predict changes in EMP of BRIC countries. This negative effect of uncertainty on exchange rates also aligns with Krol (2014) and Kido (2016), both showed that high uncertainty leads to high exchange rate volatility.…”
Section: Resultsmentioning
confidence: 95%
“…Despite this recognition of the effects of uncertainty on real exchange rates, the literature is limited. Recently, Olanipekun, Güngör, and Olasehinde-Williams (2019) showed that there is some form of feedback causal relationship between EMP and EPU in BRIC countries, but none has existed on the degree and direct impact of EPU on EMP. This necessitates the need to investigate EMP response to uncertainty resulting from economic policy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Olanipekun et al (2019a) also established a causal relationship between domestic EPU and EMP among the BRIC countries and showed that global EPU can significantly explain the movements in EMP of the BRIC countries. However, to our knowledge, specific evidence on how the EMP is associated with uncertainty arising from the United States has not been established.…”
mentioning
confidence: 85%